2023
DOI: 10.1093/asjof/ojad043
|View full text |Cite
|
Sign up to set email alerts
|

Objective Analysis of Age-Related Changes in the Superficial Musculoaponeurotic System in Japanese Females Using Computed Tomography

Abstract: Background The superficial musculoaponeurotic system (SMAS) is an anatomical structure involved in facial aging. Objectives This study focused on SMAS thickness, and aimed to establish age-related changes in SMAS thickness. Methods A total of 100 adult Japanese female participants (aged 20–79 years) were enrolled in the study. The participants were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A 2020 study fed rats with fewer calories than their ad-libitum counterparts and found that 57% of the age-related genetic changes that occurred in normal rats did not occur in calorie-restricted rats [49]. MRI or CT imaging of SMAS are also evolving to demask its implications into the phenomena of the aging face [50][51][52].…”
Section: Anatomical Base Of Modern Surgery-superficial Musculoaponeur...mentioning
confidence: 99%
“…A 2020 study fed rats with fewer calories than their ad-libitum counterparts and found that 57% of the age-related genetic changes that occurred in normal rats did not occur in calorie-restricted rats [49]. MRI or CT imaging of SMAS are also evolving to demask its implications into the phenomena of the aging face [50][51][52].…”
Section: Anatomical Base Of Modern Surgery-superficial Musculoaponeur...mentioning
confidence: 99%